High-definition transcranial direct current stimulation of the left middle temporal complex does not affect visual motion perception learning - Wu, Di; Wang, Yifan; Liu, Na; Wang, Panhui; Sun, Kewei; Xiao, Wei (Frontiers in Neuroscience, 2022)
Visual perceptual learning (VPL) refers to the improvement in visual perceptual abilities through training and has potential implications for clinical populations. However, improvements in perceptual learning often require hundreds or thousands of trials over weeks to months to attain, limiting its practical application. Transcranial direct current stimulation (tDCS) could potentially facilitate perceptual learning, but the results are inconsistent thus far. Thus, this research investigated the effect of tDCS over the left human middle temporal complex (hMT+) on learning to discriminate visual motion direction. Twenty-seven participants were randomly assigned to the anodal, cathodal and sham tDCS groups. Before and after training, the thresholds of motion direction discrimination were assessed in one trained condition and three untrained conditions. Participants were trained over 5 consecutive days while receiving high-definition tDCS (HD-tDCS) over the left hMT+. The results showed that the threshold of motion direction discrimination significantly decreased after training. However, no obvious differences in the indicators of perceptual learning, such as the magnitude of improvement, transfer indexes, and learning curves, were noted among the three groups. The current study did not provide evidence of a beneficial effect of tDCS on VPL. Further research should explore the impact of the learning task characteristics, number of training sessions and the sequence of stimulation.